ELIV-MarketPlace 2022: - VDI Wissensforum GmbH (VDI Verlag, 2022)
Contents E/E in Passenger Cars Energy Management Benchmark of modern electrification concepts – Which powertrain topologies have the most benefits? ..... 1 Architecture/Engineering – Testing Virtual E/E Test Platform – co-exploration, optimization and validation of ECU architecture and software in the context of the car ..... 9 Event Chain Analysis as a Key Competency: Efficient Development of Software-Defined Vehicles ..... 19 End-to-end Continuous Integration and Test enabled by Continental’s Cooperation Portal and Volkswagen’s Compound Test System ..... 29 Autonomous Driving in Practice – Use Cases and E periences Next-Gen Sensor Fusion for Next-Gen Sensors and Driving Functions ..... 37 Quantification of Life-Saving Collective Perception V2X Benefits ..... 59 Lessons learned from current developments of highly automated driving functions (SAE Level 3 and 4) and derivation of future success factors ..... 69 Future of Electrified Powertrain in the era of Software Defined Vehicles and Service Oriented Architecture ..... 79 An Advanced High-Efficiency Inverter wit...